The Effects of Exports, Inflation, Provincial Minimum Wage, Household Consumption, and Democracy on PMDN in Java Island for the 2009-2022 Period - Vina Rahmawati; Muhammad Ghafur Wibowo (Bulletin of Islamic Economics, 2023)
Investment is an activity that can increase economic growth in a region. In times of crisis, economic activities that can help stabilize the economy are private investment or commonly called Domestic Investment (PMDN). The purpose of this study is to determine the impact of independent variables in the form of exports, inflation, provincial minimum wage, household consumption, and the Indonesian democracy index on the variables of Domestic Investment in 6 Provinces in Java for the 2009-2022 period. The data used in this study is secondary panel data. The analysis method used is the panel data regression analysis method with a weighted Fixed Effect  model approach with Cross Section SUR. The results of this study are export variables, provincial minimum wages, and the Indonesian democracy index have a significant and positive influence on PMDN. Then the inflation variable has a negative and insignificant influence on PMDN. Meanwhile, household consumption has a significant and negative influence on PMDN in 6 provinces in Java.